Utilizing Class Points in Islamic Religious Education With A Multidisciplinary Approach - Sholihah, Ni'matus; Salamah Zainiyati, Husniyatus; Kholis, Nur (Pascasarjana Universitas KH. Abdul Chalim, 2024)
Islamic religious education is one of the disciplines that play a crucial role with significant impacts on human life, from birth in this world to one's existence in the afterlife. In its current context, especially with the rapid development of information and communication technology, the learning of Islamic religious education can be made more effective and efficient for educators, students, and educational institutions. One way to achieve this is by utilizing the Classpoint learning application software, integrated with Microsoft PowerPoint, which facilitates the delivery of instructional material through engaging presentations. This article aims to describe the utilization of the Classpoint application in Islamic religious education learning with a multidisciplinary approach. The research employs a literature review study method with data collection techniques involving literature review and the Systematic Literature Review method. Tools such as Watase Uake, EBSCO, Google Scholar, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) technique are used in the study. The research findings demonstrate that in Islamic religious education learning with a multidisciplinary approach, three perspectives – historical, anthropological, and sociological disciplines–can be effectively and efficiently conveyed through the Classpoint application.